HpFBH3 transactivates HpCO7 via binding to the E-boxes in the promoter and may accelerate flower formation in pitaya - Xiaowei Cai; Ling Xiao; Xiangmei Nie; Qiandong Hou; Sulin Wen; Kun Yang; Xiaopeng Wen (Journal of Integrative Agriculture, 2025)
Hylocereus polyrhizus, also known as pitaya or dragon fruit, is a climbing cactus grown worldwide because of its excellent performance under drought stress and appealing red-purple fruits. In practice, accelerating flower formation and inducing more flowers usually result in higher yield. However, the genes for this purpose have not been well characterized in pitaya. Previously, FLOWERING BHLHs (FBHs) have been identified as positive regulators of flower formation. In the present work, a total of eight FBHs were identified in pitaya. This is a greater number than in beet and spinach, possibly because of the recent whole-genome duplication that occurred in the pitaya genome. The phylogenetic tree indicated that the FBHs could be divided into three groups. In TYPE II, the genes of Caryophyllales encode atypical FBHs and are generated by dispersed duplication. The Ka/Ks ratios indicated that HpFBHs are under purifying selection. Promoter and expression analysis of HpFBHs revealed that they are spatiotemporally activated in flower-related tissues and responsive to multiple abiotic stresses. These results indicated that HpFBHs are involved in the flower formation of pitaya. Therefore, typical HpFBH1/3 from TYPE III and an atypical HpFBH8 from TYPE II were selected for functional verification. HpFBH3 was found to heterodimerize with HpFBH1 in the nucleus using subcellular localization, yeast two-hybrid and luciferase complementation assays. With bioinformatic analysis, all HpFBHs were predicted to transactivate downstream genes via binding to the E-boxes, which were frequently detected in the promoters of HpCOs, HpFTs and HpSOC1s. RNA-Seq datasets showed that these flowering accelerators were expressed in coordination with HpFBH3. Yeast one-hybrid and dual-luciferase reporter assays further verified that HpFBH3 transactivated HpCO7 by selectively binding to the E-boxes in the promoter. Moreover, ectopic overexpression of HpFBH3 accelerated flower formation in Arabidopsis. In summary, this study systematically characterized the typical HpFBHs, especially HpFBH3, as positive regulators of flower formation, which could be target genes for the genetic improvement of pitaya.